EFEKTIVITAS PEMANFAATAN DANA DESA DALAM MENUNJANG PEMBANGUNAN DESA DI DESA SIDOMUKTI KECAMATAN MOOTILANGO KABUPATEN GORONTALO - Joice Machmud; Sri Hantuti Paramata; Dewi Yuliyanti Ali (Universitas Muhammadiyah Gorontalo, 2021)
This study aims to determine the effectiveness of the use of village funds in supporting village development in Sidomukti Village, Mootilango District, Gorontalo District. The research method uses a qualitative research approach, with a descriptive type of research. From the results of the research, itwas found that the understanding of the program was good because it was based on the PERMENDes and PERMENDAGRI, in terms of the right target it was still ineffective because the village did not socialize the programs that had been set by the village government, the timeliness of program implementation needed to be fixed again because it was not accompanied by a planned schedule.well-structured work, the achievement of goals for the improvement of the welfare of the village community, and has been carried out properly through self-management mechanisms, and the last, in terms of real change, has appeared in accordance with conditions in the field, the community caneasily obtain health, education and public services.Keywords: Village Fund, Effectiveness, Utilization